From Mud to Megabytes: A Narrative Journey of Digital Transformation and Data Management Resilience at SD Negeri Tambakrejo 03 Semarang - Wisnu Yuli Setianingsih; Nurkolis Nurkolis; Muhammad Prayito; Waewalee Waewchimplee (Yayasan Adra Karima Hubbi, 2026)
Background. Digital transformation requires schools to manage information efficiently and securely. However, many elementary schools still rely on fragmented paper-based records that are vulnerable to loss and damage. At SD Negeri Tambakrejo 03 Semarang, recurring floods exposed the fragility of conventional data management and highlighted the need for a more resilient digital solution. Purpose. This study aimed to develop the Pusporejotiga application as an integrated platform for school data management and to evaluate its feasibility, practicality, and effectiveness. Method. This study employed a Research and Development (R&D) approach using the Borg and Gall model. The research involved the principal, teachers, and administrative staff. Data were collected through interviews, observations, questionnaires, and documentation and analyzed using qualitative and quantitative techniques. Results. The Pusporejotiga application achieved a feasibility score of 90%, indicating that it was highly suitable for implementation. User evaluations produced an average practicality score of 4.46 out of 5, demonstrating a very high level of usability. The average effectiveness score increased from 53.8 before implementation to 89.0 after implementation, representing a 65.4% improvement. The application improved data accessibility, information organization, reporting efficiency, and data security while reducing administrative workload. It also transformed a context characterized by document vulnerability and fear of data loss into a model of digital resilience. Conclusion. The Pusporejotiga application effectively supports digital transformation and strengthens organizational resilience. The model provides a practical framework for protecting educational data and improving administrative performance, particularly in schools facing environmental risks such as flooding.